The everything personal finance in your 40s & 50s book : a comprehensive strategy to ensure you can retire when you want and live well - Lane, Jennifer, 1967- (Everything series., 2009)
Have you gotten a late start on your retirement preparations? Are you worried about your fiscal future? This valuable guide helps you to: create and stick to a budget; invest wisely; pay for college while still saving for retirement; help your kids with debt (without putting yourself in debt); talk to your parents about wills and money; make the most of your working income.